Moulding a villain in billion dollar whale: a post-humanist approach - Seach, Jin Beng; Ira Zuliana Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The advancement of the human race and the emergence of new ideologies/movements often come hand in hand. Post-humanism is a concept whose origin can be traced to the 1980s when people began to challenge the long-established views of humanism. Humanism emphasises that the world be evaluated through a fixed moral hierarchy where the human species must be placed on top of it. On the contrary, post-humanism challenges this view by highlighting the importance of redefining what it means to be human. It urges people to embrace different identities and see the world beyond its basic dualistic nature. This paper examines how post-humanistic ideas can be employed as tools to mould the villain, Jho Low, in Tom Wright’s and Bradley Hope’s Billion Dollar Whale. This article draws on ideas from Donna Haraway (1985) in relation to the concept of ‘cyborg’ and Francesca Ferrando’s (2019) discussion on post-dualism that breaks the categorical differences between humans and other non-human objects. It argues that the book’s villain, Jho Low, has been transformed so significantly that he is no longer bound by his origins, physical presence, and abilities attributed to humans, eventually rendering him invincible. It also highlights the idea that, just as with any other human, villains evolve, too, offering a different perspective through the post-humanistic lens.